Transparency and Accountability of Village Fund Management: A Case Study in Maitara Tengah Village City Of Tidore Islands - Rheza Pratama Konoras; Ririn Demayanti; Titiek Arafiani Ruray (Universitas Sulawesi Barat, 2021)
This study aims to explore whether the management of village funds in Desa Maitara Tengah, Tidore Islands City has been carried out in transparent and accountable manner or not. This was motivated by a decrease in the Village Revenue and Expenditure Budget (Indonesian: Anggaran Pendapatan dan Belanja Desa/APBDesa) in 2020, which may have been due to non-transparent and accountable management. For this reason, a total of 70 questionnaires were distributed to villagers, who were at least 17 years old. By using the descriptive analysis method, the results show that the management of village funds has been carried out transparently andaccountability, both in the planning, implementation, administration, reporting, and accountability processes. Thus, the decline in village budget and expenditure in 2020 was not caused by non-transparent and accountable managers, but by other factors that were not discussed in this study.